Parametric investigation on an off-centre braced frame system's stiffness - Mosalman, H.; Sulong, No.R. (Academic Journals, 2010)
In this paper, a particular off-centre braced (OCB) system subjected to lateral load, which induced compressive force to the brace elements is examined. This bracing system consists of three members, where the diagonal member is not straight and it is connected to the corner of the frame by a third member. The out-of-straightness of the diagonal members will introduce eccentricity to the system. This system improves the energy dissipation due to earthquake as well as its eccentricity allows architects to have more openings in the panel areas. In this regard, the location of connection point of the three braced elements that is the eccentricity, considering the opening dimensions has significant effect on the stiffness of the system. In order to assess the influence of the connection position and other parameters such as cross-section area of the brace elements and span/ height ratio of the frame on the stiffness of the system, analytical studies to obtain the stiffness equations have been developed. The results indicate that as the eccentricity increasing (connection point moves closer to the corner of the frame), the frame's stiffness decreases. Also, the cross-section area of the third member has a significant role on the stiffness of this system and can make up the stiffness elimination due to increasing eccentricity of the connection point. In addition, a range of values in locating the brace elements connection point is introduced, which could be helpful for designers.